Management Pengoptimalan Kebutuhan Oksigen Pada Pasien Gagal Jantung Di Unit Perawatan Intensif: A Literatur Review - Linggar Pangukir Rahayu (Jurnal Berita Ilmu Keperawatan, 2020)
Heart failure occurs with symptoms associated with an impaired myocardial ventricular function other than that heart failure manifests as vascular congestion in the pulmonary and systemic circulation resulting in symptoms of insufficient circulation. The main treatment in patients with heart failure with sufficient oxygenation needs. Objective: to find out how to optimize the oxygen needs of heart failure patients. Method: This study uses a literature review method that focuses on fulfilling the oxygen needs of heart failure patients by searching Google Scholar, Elsevier, and Pubmed by using keywords heart failure, oxygenation, respiratory, and heart rate in the period 2015 - 2020. Results: the search found more than 500 case reports according to keywords and then filtered, obtained 5 case report articles. The journal describes the case of heart failure patients and how to cope with oxygen demand in heart failure patients who often experience shortness of breath or hypoxemia. Conclusion: oxygenation therapy for heart failure patients can be done by using ventilation aids and adjusting the patient's position according to the patient's condition and complications